Stochastic frontier modelling of technical efficiency and input elasticities in independent broiler production systems in Sorong Regency, Indonesia - Lokden, Salmon; Pakage, Stepanus; Pattiselanno, Fredy; Wajo, Mohammad; Baaka, Alnita; Iyai, Deny; Manik, Hotlan; Suawa, Elfira K.; Rahayu, Bernadetta W. I. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
This study assessed the production performance and technical efficiency of independent broiler farmers in Sorong Regency, Indonesia, using a stochastic frontier framework. The objective of the research is to quantify the influence of major production inputs on output, estimate technical efficiency levels, and evaluate the extent to which inefficiency contributes to variations in broiler performance under open-house production conditions. Primary data were collected from active broiler farmers and analyzed using a Cobb–Douglas stochastic frontier production function estimated through maximum likelihood procedures to obtain input elasticities and individual efficiency scores. The results indicated that broiler production performed competitively, with a performance index of 456, low mortality, and an efficient feed conversion ratio. The production frontier estimation showed that day-old chicks and feed were the dominant determinants of output, while medication, electricity, and fuel inputs did not exert statistically significant effects. Average technical efficiency reached 0.89, with 86.6 percent of farmers operating at high-efficiency levels. The gamma parameter of 0.83 indicated that most output variation stemmed from technical inefficiency rather than random disturbances, underscoring the relevance of managerial capacity in shaping production outcomes. The study concludes that improving the quality of biological inputs and strengthening managerial practices is essential for sustaining productivity among independent broiler farmers. The findings provide empirical guidance for technical training programs, input quality improvement, and targeted interventions to enhance production efficiency in eastern Indonesia.